Study of Important Operating Parameters for the Adsorption of Acrylic Acid from Wastewater Using Palm Ash - Nuradibah , Hussin; Cheng, C. K.; Anwaruddin, Hisyam (Asian Network for Scientific Information, 2014)
The potential of the agriculture waste residue, palm ash as an adsorbent to remove Acrylic Acid (AA) was investigated in the present study was identified. Palm ash was treated by reflux with sulfuric acid before the adsorption. Batch adsorption study was conducted to study the effect of various operating parameters such as adsorbent dosage, initial concentration of AA, temperature and contact time. The experimental data were correlated to the Langmuir and Freundlich models of adsorption. Isotherm data were fitted well with Freundlich model. The maximum adsorption capacity of AA onto palm ash was obtained as qm = 1.98 mg g-1 with an optimum palm ash dosage w = 200 g L-1 at 303K for C0 = 100 mg L-1. The results indicate that palm ash is suitable as adsorbent to remove AA from aqueous solutions.